Central noradrenergic mechanisms and the acute stress response during painful stimulation. (December 2014) - Chapman, C Richard; Bradshaw, David H; Donaldson, Gary W; Jacobson, Robert C; Nakamura, Yoshio
Events that threaten tissue integrity including noxious stimulation activate central noradrenergic circuits, particularly locus coeruleus and its projections. Recent advances in theory hold that an adaptive, defensive shift in brain activity takes place in response to threat. In principle, this shift may accentuate the autonomic and central biomarkers of the perception of painful events and the experience of pain itself. We have examined the effects of an alpha-2 agonist on pupil dilation responses, skin conductance responses, near field somatosensory evoked potentials and pain reports in normal volunteers undergoing repeated trials of painful fingertip stimulation delivered at low, medium and high intensities. In a double-blinded study, 114 healthy male and female volunteers underwent repeated noxious stimulation under baseline, placebo and active drug conditions where the active drug was the alpha-2 agonist tizanidine 4 mg. In contrast to baseline and placebo conditions, tizanidine 4 mg significantly reduced the magnitudes of the mean pupil dilation response, the mean skin conductance response, the mean near field somatosensory evoked potential peak-to-peak amplitude and the mean pain intensity rating. Stimulus intensity significantly altered all three biomarkers and the pain report in a graded fashion. There were no sex differences. These findings support the hypotheses that painful events activate central noradrenergic circuits, and that these circuits play a role in the autonomic and central arousal associated with pain.